A scientometric, bibliometric, and thematic map analysis of hydraulic calcium silicate root canal sealers - Anastasios Katakidis; Konstantinos Kodonas; Anastasia Fardi; Christos Gogos (Restorative Dentistry & Endodontics)
ObjectivesThis scientometric and bibliometric analysis explored scientific publications related to hydraulic calcium silicate-based (HCSB) sealers used in endodontology, aiming to describe basic bibliometric indicators and analyze current research trends.Materials and MethodsA comprehensive search was conducted in Web of Science and Scopus using specific HCSB sealer and general endodontic-related terms. Basic research parameters were collected, including publication year, authorship, countries, institutions, journals, level of evidence, study design and topic of interest, title terms, author keywords, citation counts, and density.ResultsIn total, 498 articles published in 136 journals were retrieved for the period 2008–2023. Brazil was the leading country, and the universities of Bologna in Italy and Sao Paolo in Brazil were represented equally as leading institutions. The most frequently occurring keywords were “calcium silicate,” “root canal sealer MTA-Fillapex,” and “biocompatibility,” while title terms such as “calcium,” “sealers,” “root,” “canal,” “silicate based,” and “endodontic” occurred most often. According to the thematic map analysis, “solubility” appeared as a basic theme of concentrated research interest, and “single-cone technique” was identified as an emerging, inadequately developed theme. The co-occurrence analysis revealed 4 major clusters centered on sealers’ biological and physicochemical properties, obturation techniques, retreatability, and adhesion.ConclusionsThis analysis presents bibliographic features and outlines changing trends in HCSB sealer research. The research output is dominated by basic science articles scrutinizing the biological and specific physicochemical properties of commonly used HCSB sealers. Future research needs to be guided by studies with a high level of evidence that utilize innovative, sophisticated technologies.